Evaluation Of The Fresh Friday Program on The Healthy Living Culture of Students At 1 Bumi Harjo State Elementary School - Hartini Hartini; Nurul Hikmah Kartini; Hendri Hendri (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
Aim: This study aimed to evaluate the effectiveness of the Jumat Segar Program in developing healthy living habits among students at 1 Bumi Harjo State Elementary School using the CIPP (Context, Input, Process, Product) evaluation model. Method: The study employed a qualitative approach with evaluative research methods. Research subjects consisted of the principal, physical education teacher, classroom teachers, and students. Data collection techniques included interviews, observations, and documentation. Program effectiveness was assessed using success indicators, including increased student participation, improved discipline, the development of healthy lifestyle habits, increased awareness of personal and environmental health, and the strengthening of positive character traits. Result and Discussions: The findings revealed that: (1) the context aspect indicated that the program was implemented based on students’ real needs in improving physical fitness and healthy lifestyle habits and was relevant to the school’s vision and mission; (2) the input aspect showed that the program was supported by human resources, facilities, and adequate planning although several limitations remained in facilities and instructor competence; (3) the process aspect demonstrated that the activities were implemented routinely and systematically through morning exercise, healthy eating, environmental cleaning, and health education, although student participation had not been fully equal; and (4) the product aspect indicated positive changes in students’ healthy lifestyle behaviors, particularly in exercise habits, cleanliness, discipline, and environmental awareness. Conclusion: Based on the evaluation results, the Jumat Segar Program was considered effective in gradually and sustainably developing a healthy living culture among students.